Towards an inclusive digital transition: Industry 4.0 as a lever for equitable development in Algeria - Rachedi, Akila (International journal of economic perspectives, 2025)
This research examines the role of Industry 4.0 in promoting inclusive growth, highlighting its opportunities and risks. The aim is to assess how advanced technologies (artificial intelligence, robotics, big data, IoT) can boost industrial productivity while promoting a more equitable distribution of economic and social benefits. The methodology is based on an in-depth review of academic and institutional literature. The results show that Industry 4.0 offers significant prospects in terms of competitiveness, environmental sustainability and the creation of skilled jobs. However, it also entails major risks: accentuating inequalities between countries, digital exclusion, destruction of low-skilled jobs and increased technological dependency. To make it a lever for inclusive development, the study recommends the implementation of appropriate public policies, focusing on training, digital infrastructure development, international cooperation and social protection for workers affected by the digital transition.